Psychotropic Drug Use among Children: A Comparison of ADHD Drug Use in the Nordic Countries and the Effect of ADHD Drug Treatment on Academic Progress - Helga Zoëga 1976- (2011)
Abstract Attention-deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder affecting 5-10% of school-aged children. Drug treatment for ADHD with stimulants is now widely used as a therapeutic option in the US and increasingly in Europe. Nevertheless, the increasing use of ADHD drugs is debated, chiefly because of concerns of over-use, addiction and uncertainty of the long-term outcomes of treatment. Although research in pediatric psychopharmacology has expanded during the past decade, utilization studies have typically rested on limited data sources. Thus, the evidence base for prevalence of use and treatment safety, as well as long-term risks and effectiveness of many psychotropic agents for children remains fragmented. The long-term effects of stimulant treatment are largely unknown and evidence about their effect on academic progress among children with ADHD is limited. Our studies are based on the unique setting in Iceland, the nationwide prescription drug registries now available in all Nordic countries and the rare opportunity of record linkage to national scholastic examinations in Iceland. We aimed to investigate patterns of psychotropic drugs use among the total pediatric population in Iceland, to compare ADHD drug use among all Nordic countries and, finally, to address whether children’s academic progress is affected by the initiation of stimulant treatment for ADHD. In Study I we found a markedly high prevalence between 2003 and 2007 of psychotropic drug use among children in Iceland (48.7 per 1000 in 2007). Stimulants and antidepressants were the two most commonly used psychotropic drugs in 2007, respectively with a prevalence of 28.4 and 23.4 per 1000 children. A statistically significant trend of declining prevalence and incidence of antidepressant use occurred during the study period, while prevalence increased for use of stimulants and antipsychotics. Out of 21,986 psychotropic drugs dispensed in 2007, 25.4% were used off-label for children. In Study II we compared national use in ...